Multilevel modelling - Skrondal, Anders; Rabe-Hesketh, S.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2010)
Data collected in the social sciences often have a multi-level or clustered structure, which creates multi-level questions and analyses. The editors of this work pull together the various types, complex issues and design of multi-level modelling.
v. 1. Linear multilevel models : model formulation and interpretation -- v. 2. Linear multilevel models : inference, diagnostics and design -- v. 3. Multilevel generalized linear models -- v. 4. Complex models and issues.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Social sciences -- Statistical methods; Multilevel models (Statistics); Social sciences -- Research -- Methodology; Electronic books